Spatial variation, multi-meteorological factors and potential source analysis of air pollutants in Chengdu megacity of Chengdu-Chongqing economic circle - Li, Xiaoju; Abdullah, Luqman Chuah; Hu, Jinzhao; Sobri, Shafreeza; Md Said, Mohamad Syazarudin; Hussain, Siti Aslina; Aun, Tan Poh (Springer, 2024)
Affected by unique topography, meteorological factors and high emission sources, it is crucial to have an in-depth understanding of the air pollution characteristics of Chengdu megacity. This research investigated the spatial evolution features of the six criteria pollutants in Chengdu from 2014 to 2020. The relationship between air pollutants and multi-meteorological factors also will be systematically elucidated. Together with the backward trajectory model, the potential source areas of PM2.5 and O3 were further simulated. The results revealed that there is spatial heterogeneity in the distribution of air pollution in Chengdu. Besides, the concentrations of PM2.5, PM10, SO2, NO2 and CO are only positively correlated with pressure. While, O3 only shows a negative correlation with relative humidity and pressure. Furthermore, regional transport is also one of the important contributing sources of PM2.5 and O3. This study can accurately grasp the status of regional air pollution, and provide accurate and feasible solutions for the collaborative reduction of air pollution in the Cheng-Yu area. Furthermore, it provides data references for exploring efficient air pollution control measures in complex terrain, and also accumulates some experience for the megacities of similar situations in the world.